Influence of Corporate Governance, Executive Character, Sales Growth and Company Size Against Tax Avoidance - Maula, Palupi Iamatul; Benarda (EAJ (Economic and Accounting Journal), 2025)
This study aims to determine the Influence of Corporate Governance on Independent Commissioners and Audit Committees, Executive Character, Sales Growth, and Company Size on Tax Avoidance. Tax Avoidance is a dependent variable and Corporate Governance, Executive Character, Sales Growth, and Company Size are independent variables. This type of research was carried out using quantitative methods and purposive sampling data collection techniques. The population in this study is all property and real estate companies listed on the Indonesia Stock Exchange during the period 2019-2023. The number of companies used as a research sample is 14 companies. The analysis method uses multiple regression analysis, F test and T test using Eviews 12. The results of the study show that Corporate Governance which is proxied to Independent Commissioners and the Audit Committee has no effect on Tax Avoidance, Executive Character has no effect on Tax Avoidance, Sales Growth has no effect on Tax Avoidance and Company Size has no effect on Tax Avoidance. Meanwhile, Corporate Governance which is proxied against Independent Commissioners and Audit Committees, Executive Character, Sales Growth, and Company Size have a significant simultaneous effect on Tax Avoidance.